ANALISIS PRAKTIK KHATAM AL-QUR'AN PADA BULAN RAMADHAN DAN DI PERKUBURAN PERSPEKTIF TEOLOGIS DAN SOSIAL - Hafizh Idri Purbajati; Sawaluddin Siregar; Maraondak Pangestu; Dahniar Namora (Yayasan Baitul Hikmah al-Zain, 2025)
Khatam is a communal tradition frequently practiced by reciting the verses of the Qur’an from the opening chapter to the end. This study examines two commonly observed Qur’anic reading traditions among Muslims: completing the Qur’an (khatam) during the month of Ramadan and completing the Qur’an in the ritual of “seven days and seven nights” at the gravesite of a deceased person. The main issue explored is the distinction between these two practices in terms of their conformity with Islamic teachings and their implications for public understanding. Completing the Qur’an in Ramadan is widely regarded as a meritorious practice due to the month’s blessed nature, whereas the practice of completing the Qur’an over seven days and seven nights at a graveyard is often subject to scrutiny, particularly regarding its legal basis in Islamic jurisprudence. The research employs a qualitative approach, drawing upon hadith analysis, Qur’anic interpretation, and scholarly opinions concerning both practices. The study also incorporates an interview with an informant familiar with the local tradition. The findings indicate that completing the Qur’an during Ramadan is strongly supported by numerous hadiths and the practices of the Companions, making it a recommended devotional act. Meanwhile, the practice of completing the Qur’an for seven days and nights at a gravesite does not have a clearly established foundation in Islamic law. However, among the four Sunni legal schools, two—Imam al-Shafi‘i and Imam Ahmad ibn Hanbal—hold the view that reciting the Qur’an at gravesites is permissible and even encouraged. According to these scholars, praying for the deceased, particularly by family members, is highly recommended.